OP22 Alcohol in suicides and self-harm: findings from the suicide support and information system and the national registry of deliberate self-harm ireland. (31st August 2015) - Griffin, E; Larkin, C; McAuliffe, C; Corcoran, P; Willamson, E; Perry, I; Arensman, E
Abstract : Background: Alcohol misuse is a significant risk factor for both self-harm and suicide, and alcohol is often involved in self-harm acts and present at time of deaths by suicide. This study sought to identify factors associated with alcohol consumption in both non-fatal self-harm presentations and cases of suicide. Methods: This study included suicides in Cork, Ireland between September 2008 and June 2012 and self-harm presentations from January 2007 to December 2013. 8145 Emergency Department presentations involving self-harm during this period were recorded by the National Registry of Deliberate Self-Harm. Alcohol involvement in self-harm presentations was ascertained from medical notes. 307 cases of suicide during this period were recorded by the Suicide Support and Information System. Alcohol involvement in suicides was ascertained from toxicology results. Results: Alcohol consumption was evident in 21% of self-harm presentations and in 44% of suicide cases. Univariate analysis indicated that variables associated with having consumed alcohol in a self-harm presentation were: gender, age, method of self-harm, type of aftercare received and timing of the presentation. In a multivariate model, a number of variables remained significant. Self-harm patients who consumed alcohol at time of presentation were more likely to be male (OR = 1.24, 95% CI: 1.10–1.40) and least likely to present with self-cutting (OR = 0.45, 95% CI: 0.38–0.54). Presentations with alcohol involved were less likely to be admitted to a psychiatric ward (OR = 0.60, 95% CI: 0.44–0.81) and less likely to present during the daytime (OR = 0.50, 95% CI: 0.43–0.58), and at the weekend (OR = 1.23, 95% CI: 1.09–1.40). For suicide cases, univariate analyses indicated that the only variable associated with having consumed alcohol was younger age (>65 years = ref: <25 years OR = 8.61, 95% CI: 2.35–31.55; 25–44 years OR = 11.05, 95% CI: 3.16–38.73; 45–64 years OR = 4.23, 95% CI: 1.19–15.09); male gender approached statistical significance (OR = 1.80, 95% CI: 0.98–3.29). All other variables (marital status, living arrangements, suicide note, method of suicide, drugs in toxicology) had no significant association with alcohol consumption among suicides. Conclusion: This study underlines the high frequency of alcohol involvement among those engaging in fatal and non-fatal suicidal behaviour. Alcohol involvement was associated with male gender in both suicides and self-harm presentations. Public health measures to restrict access to alcohol may be used to enhance suicide prevention, given that ecological studies show reduced suicide rates following measures to restrict access to alcohol. Active consultation and collaboration between the mental health services and addiction treatment services should be arranged in the best interests of those who present with dual diagnosis.